Can Human Rights Monitoring Halt Abuses in Sri Lanka? - Alston, Philip; Abresch, William (Tufts Archival Research Center, 2005)
Volume 31, Issue 2. Summer In the Sri Lankan conflict, taking substantial steps to promote human rights accountability could also have a positive impact on the overall peace process. In this context, international human rights monitoring could play an important role by providing some immediate protection to the population and helping establish the conditions for a sustainable peace.